Pengaruh Budaya Organisasi Dan Komitmen Organisasi Terhadap Turnover Intention (Studi PT. Tri Mitra Jaya Sentosa) - Kokoh Iman Sari; Budi Wahono; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstrackThis research was conducted at PT. Tri Mitra Jaya Sentosa. The type of research used is quantitative research where the data are expressed in numbers and analyzed by statistical techniques. The purpose of this study was to determine the effect of organizational culture and organizational commitment on turnover intention. The independent variables used are organizational culture and organizational commitment, while the variables used are intention to move. The sample used in this study were 36 respondents who are employees who work at PT. Tri Mitra Jaya Sentosa. Data collection techniques used was a questionnaire. The analytical methods used were instrument test, morality test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 25 computer software for data processing. The results of this study indicated that organizational culture has a positive and significant effect on turnover intention, organizational commitment has a positive and significant effect on turnover intention. Keywords: Education Level, Age and Work Productivity